Rethinking Representation and Animation - Erik Solfeldt; Anna Naglaya (Current Swedish Archaeology)
Archaeological interpretations of prehistoric humanoid figurines, made and used by the hunter-gatherers of the Stone Ages, have traditionally relied on Western concepts of hylomorphism and iconology. Consequently, these figurines are depicted as finished and static objects of art, often separated from their archaeological contexts. Analysis of these figurines has been focused on identifying what they represent, rather than considering what they do or how people used them. This paper draws on new animism and Indigenous knowledge, combined with visual ethnographic analysis to create a visual ethnoarchaeology of northwestern Siberian humanoid figurines, here viewed as material spirits, within their animistic contexts. We argue that archaeologists’ interpretative focus on representation should be abandoned in favour of attending to animation and the material and immaterial ecological relations these figurines shared with their prehistoric makers.